Search IntMath
Close

450+ Math Lessons written by Math Professors and Teachers

5 Million+ Students Helped Each Year

1200+ Articles Written by Math Educators and Enthusiasts

Simplifying and Teaching Math for Over 23 Years

# 2. Graphs of Linear Functions

It is very important for many math topics to know how to quickly sketch straight lines. When we use math to model real-world problems, it is worthwhile to have a sense of how straight lines "work" and what they look like.

We met this topic before in The Straight Line. The following section serves as a reminder for you.

## a. Slope-Intercept Form of a Straight Line: y = mx + c

If the slope (also known as gradient) of a line is m, and the y-intercept is c, then the equation of the line is written:

y = mx + c

### Example 1

The line y = 2x + 6 has slope m = 6/3 = 2 and y-intercept c = 6.

Graph of the linear equation y = 2x+6.

## b. Intercept Form of a Straight Line: ax + by = c

Often a straight line is written in the form ax + by = c. One way we can sketch this is by finding the x- and y-intercepts and then joining those intercepts.

### Example 2

Sketch the line 3x + 2y = 6.

The x-intercept (that is, when y = 0) is:

3x = 6

This gives:

x = 2.

The y-intercept (that is, when x = 0) is:

2y = 6

This gives:

y = 3.

Joining the intercepts (2, 0) and (0, 3) gives the graph of the straight line 3x + 2y = 6:

Graph of the linear equation 3x + 2y = 6.

## Slope of a Line

The slope (or gradient) of a straight line is given by:

m=text(vertical rise)/text(horizontal run)

We can also write the slope of the straight line passing through the points (x1, y1) and (x2, y2) as:

m=(y_2-y_1)/(x_2-x_1)

Using this expression for slope, we can derive the following.

## c. Point-slope Form of a Straight Line: y − y_1= m(x − x_1)

If a line passes through the point (x1, y1) and has slope m, then the equation of the line is given by:

y − y_1= m(x − x_1)

### Example 3

Find the equation of the line with slope −3, and which passes through (2, −4).

Here,

m = −3,

x_1= 2, and

y_1= −4.

So using the formula y − y_1= m(x − x_1), the equation is

y − (−4) = −3(x − 2)

y + 4 = 3x + 6

y = 3x + 2

The graph is:

Graph of the linear equation y = -3x+2.

## Problem Solver This tool combines the power of mathematical computation engine that excels at solving mathematical formulas with the power of GPT large language models to parse and generate natural language. This creates math problem solver thats more accurate than ChatGPT, more flexible than a calculator, and faster answers than a human tutor. Learn More.